Some Recent Advances in Liquefied Natural Gas (LNG) Production, Spill, Dispersion, and Safety - Ikealumba, W.; Wu, Hongwei (American Chemical Society, 2014)
The global demand of liquefied natural gas (LNG) has risen rapidly in recent years for the reasons of energy security and sustainable development. This has led to considerable recent research interests and efforts in the LNG production chain and associated risks in handling, storage, and transport of LNG, largely driven by the intrinsic process safety issues of LNG, potential terrorist threats, and public confidence in LNG safety. This review presents an overview on some recent advances in the LNG value chain, covering upstream gas production and gathering, liquefaction, shipping, and regasification processes. Recent developments in the experimentation and modeling of LNG spills associated with the LNG value chain are then summarized, covering the events following a LNG spill, including LNG pool formation, vapor dispersion, and combustion. The consequent hazards and safety issues are also discussed, with a focus on the methods for improving the safety of personnel, facilities, and ships. The key technical gaps in the related research areas have been identified, and future research directions are outlined.